Insects as bio-inspiration - Qamaruz Zaman, Faridah; Baharuddin, Nasir; Mohd Tahir, Osman (Universiti Putra Malaysia Press, 2013)
From the dawn of time, mankind has always looked upon his surroundings and observed other beings like the fauna and flora going about their lives. This in turn, piques our curiosity to understand the mechanisms and procesess entailed in fashioning a product. Often times, these creatures are more in tune with nature and thus able to build or make things that they need in harmony with their habitats. To date only 1 out of 10 insect species have been identified. This means for the million insect species out there, 900,000remains unknown. The sheer magnitude of discoveries and potential bioinspirations yet to be explored is mind-boggling.